Analysis of complications of endovascular recanalization in patients with chronic coronary occlusion - E. V. Aksenov; V. B. Golovenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Duration of occlusion was determined from the moment of myocardial infarction in the basin of the infarct-linked coronary artery (CA). The duration of occlusion from 3 to 6 months was observed in 26.8% of patients (98 patients). The period of occlusion from 6 to 12 months was registered in 37.5% of patients (137 people). The total duration of occlusion from 1 year to 3 years was 35.6% of patients (130 patients). As a result of the performed research, it was determined that the highest percentage of complications in the study group was in the MI (1.1% of cases). At the heart of the development of this complication was the impossibility of effectively recanalizing the occluded CA and the duration of the angiographic procedure. In this case, the incidence of MI was comparable between procedures that had 100% angiographic success and in procedures that prevented an effective recanalization. In comparison with successful procedures, unsuccessful procedures had significantly higher rates of «large» periprocedural complications. The highest percentage of «small» complications included contrast-induced nephropathy (4.9%), minor bleeding (3.28%), and complications from vascular access that did not require surgical correction (1.1%).